IMPLEMENTASI METODE QUANTUM HIJAIYAH DALAM PENGENALAN HURUF HIJAIYAH PADA PESERTA DIDIK KELAS II SDN 22 SULUR MEDAN TAHUN AJARAN 2024-2025 - Surti; Suhari; Mutazam (Lunggi Journal, 2026)
This research was motivated by students' low ability to recognize the hijaiyah letters, necessitating the need for effective and engaging learning methods. The researcher attempted to apply the Quantum Hijaiyah method as a solution in the learning process in second-grade students at SDN 22 Sulur Medan, Academic Year 2024-2025. The research problem formulation includes the planning and implementation of the method in recognizing the hijaiyah letters. The goal is to improve the learning process of Islamic Religious Education. This study used a Classroom Action Research (CAR) model with observation and testing techniques to measure student learning outcomes. The results of the study showed a significant improvement: in cycle I, the completion rate increased from 23% (pretest) to 85% (posttest), and in cycle II it increased from 76% (pretest) to 92% (posttest). Thus, the application of the Quantum Hijaiyah method has been proven to improve students' understanding of the Hijaiyah letters and overall learning outcomes.